Brief report: caregivers’ well-being in families with neurodevelopmental disorders members during COVID-19: implications for family therapy - Sousa, Daniela; Ferreira, Ana; Sequeira, Joana; Monteiro, Marilyn J.; Simões, Marco; Castelo-Branco, Miguel (Frontiers in Psychiatry, 2024)
Neurodevelopmental disorders affect the lifespan of diagnosed individuals and their families. COVID-19 challenged these families with daily routine unpredictability requiring rapid adaptations. Moreover, associations and schools were closed, leaving these families without regular social support. Here, we investigate which individual and family factors can predict the caregiver's depressive state and overall burden. An online study took place between 2021 and 2022. 32 caregivers (30 females; 48±8.22 years old; range 26 to 63 years old) reported having a family member with a neurodevelopmental disorder, the majority diagnosed with autism spectrum disorder. Caregivers responded to a protocol to assess the burden, resilience, depressive, anxious, and stress symptomatology, as well as the behavior of the diagnosed individual. Hierarchical multiple regressions were performed to identify protective and risk factors for the caregivers' wellbeing. Caregiver's depressive state was explained by 29.3% of the variance of the family cohesion factor, indicating that high levels of balanced family cohesion represent a crucial protective factor for reducing caregiver's depressive state. Additionally, overall caregiver burden was explained by 17.8% of the variance due to self-perception and 26.4% due to family cohesion, with the caregiver's self-perception playing an important protective role in the overall perception of burden. The proportion of male and female respondents seems to corroborate the significant role of women in caregiving. These results emphasize the importance of considering both individual and family factors of caregivers during interventions, which have implications for family therapy with families of members diagnosed with neurodevelopmental disorders, specifically with autism.